Ādivāsī asmitā : prabhutva aura pratirodha - Luguna, Anuja, 1986- (Dillī : Ananya Prakāśana, 2015)
Contributed articles on the plight and struggle of Adivasis in India and their portrayal in literature.
In Hindi.
Keywords: Adivasis -- India -- Social conditions; Adivasis -- Social conditions; India